Psikologi Perubahan dalam Persfektif Al-Qur’an: Perilaku Manusia, Taubat, dan Transformasi Diri - Rawzalgina, Arthi Amalia; Hadi, Robi Sofian (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to explore the principles of human behavioral change, the concept of repentance (tawbah), and the process of self-transformation from the perspective of the Qur’an. Employing a qualitative approach and utilizing library research methods, this study draws upon primary sources from the Qur’an and secondary data from relevant scholarly literature, including books, journal articles, and academic papers. The findings reveal that the Qur’an strongly emphasizes positive behavioral transformation as part of a profound spiritual process rooted in self-awareness, remorse for wrongdoing, and a sustained effort toward self-improvement. Tawbah serves as a central mechanism in this transformation process. In the Qur’anic view, repentance is not merely a plea for forgiveness, but rather a comprehensive process that includes sincere regret, a firm resolve to avoid repeating the sin, and an enhancement in worship and obedience to God. Self-transformation, as a consequence of genuine tawbah, reflects a fundamental shift that encompasses spiritual elevation, self-discipline, and the internalization of Islamic values in daily life. Therefore, behavioral change, repentance, and self-transformation are interrelated components in the formation of holistic human character according to divine guidance.